I migranti e la logica del mercato - Greblo, Edoardo (SocietàMutamentoPolitica, 2020)
Almost every migratory phenomenon analysis is focused on poor and unskilled migrants. Whereas some foreigners are not considered or labelled as immigrants. Such a case particularly regards migrants with educational qualifications and job skills that accomodate the employment needs of the country of destination. In order to indicate this restricted number of people, the definition skilled migrations has been created. This phenomenon denotes the tendency to submit migratory flows to the market rationality. In this paper it is stated that the application of market rules to migrations, on the one hand encourages the tendency to think of migrants only in terms of cost-benefit analysis, while it also contributes to erode a concept of citizenship which implies equality and unlimited inclusion rights.